2015
DOI: 10.5539/ijbm.v10n7p131
|View full text |Cite
|
Sign up to set email alerts
|

The Difference between the Accounting Result and Taxable Income in Detecting Earnings Management and Tax Management: The Tunisian Case

Abstract: In this study, we examine empirically whether the gap between the pre-tax income and the taxable income predicts simultaneously earnings management and tax management. Prior researches have begun to estimate several indictors of earnings quality. We extends this works by investigating whether the book-tax differences (BTD) provides information about managerial discretion. BTD can be used as an attribute of information quality and can contain incremental information for investors and users of financial reports … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 51 publications
1
12
0
Order By: Relevance
“…Due to the different results revealed by the previous studies, this study aims to draw closer with more robustness to the research developed by Dridi and Boubaker (2015) and Tang and Firth (2011) and, thus, highlight the possible causes of the differences between the results.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Due to the different results revealed by the previous studies, this study aims to draw closer with more robustness to the research developed by Dridi and Boubaker (2015) and Tang and Firth (2011) and, thus, highlight the possible causes of the differences between the results.…”
Section: Introductionmentioning
confidence: 92%
“…These authors identified significant relationships between variables that represent proxies for (accounting and tax) EM and ABTD. Dridi and Boubaker (2015) and Tang and Firth (2011) carried out a study regarding ABTD and EM and identified a significant relationship between the variables, determining that the companies studied manage their earnings to reduce taxes.…”
Section: Introductionmentioning
confidence: 99%
“…The tax expense is one of can reduce the companies' profit and dividend for investors. Because of this, the management will do tax planning to minimize the tax expense so that company profits high (Rogers-Glabush, 2015;Alduneibat et al, 2017;Dridi & Boubaker, 2015;Hu et al, 2015;Hanlon & Heitzman 2010 ) and the firm value in the public still good (Lestari & Ward, 2015;Ylonen & Laine, 2015). However, with the enactment of expired tax collection in Indonesia for 5 years, companies in Indonesia must be prepared to encounter of tax audit and short-term tax planning will increase the tax expense from tax penalty received by company.…”
Section: Tax Planningmentioning
confidence: 99%
“…Following prior studies (Tang & Firth, 2011;Tang & Firth, 2012;Formigoni et al, 2009, Dridi & Boubaker, 2015, we separate BTD into two components, normal and abnormal differences. The reason is that abnormal differences are more informative about managerial manipulations because it represents the part which is not explained by the differences between accounting and tax treatment.…”
Section:  Dependent Variable: Btdmentioning
confidence: 99%
“…The specific characteristic of Tunisian company is that the institutional environment and the agency conflict differ from those in Anglo-Saxon countries. Tunisia is characterized by a large number of family firms, ownership concentration, the dominance of financial institutions, the authority of the state and less developed financial market (Dridi & Boubaker, 2015;Ben Amar & Abaoub, 2010).…”
Section: Introductionmentioning
confidence: 99%